The 4th Circle. - Maze, David (Optometry & Visual Performance, 2023)
In this perceptive piece on Skeffington's speech and auditory circle, I will share thoughts on my understanding of how auditory input, speech and language, and even music play a part in the testing and therapy we provide. Optometry & Visual Performance has recently reissued some of Skeffington's work. I will share my experience learning aspects of his model of vision and attempt to contextualize it for my practice as well as my own experiences.